Field based lower limb strength tests provide insight into sprint and change of direction ability in academy footballers - Jones, S.; Mullen, R.; Clair, Z.; Wrigley, R.; Andersen, T. E.; Williams, M. (Scandinavian Journal of Medicine & Science in Sports, 2021)
Conducting field-based strength assessments is embedded within football academy development processes. Yet, there is a limited understanding of how hip and groin strength assessments relate to vital game-based tasks such as sprinting and change of direction (COD) performance. Our aim was to explore field-based strength assessments and their relationships with both sprint and COD performance in male academy footballers. Participants (n = 146; age 14.2 ± 2.2 years; stature 166.3 ± 15.4 cm; body mass 55.6 ± 15.6 kg) performed maximal countermovement jump (CMJ), Nordic hamstring strength (NHS), isometric hip adductor (ADD)/abductor (ABD), 5 m, 10 m, 20 m sprints, and modified 505 agility test. All strength measures were allometrically scaled to account for body weight. Between-limb differences were reported as imbalance scores. Principal component analysis reduced sprint and COD variables to a single "running ability" component score. Scaled strength and imbalance, when controlled for age, were associated with "running ability" (adjusted R2 = 0.78, p < 0.001). Significant effects on "running ability" included the following: age, CMJ impulse, NHS, and hip-ADD. When the sprint and COD variables were explored independently, age and CMJ-impulse were featured in all sprint and COD models. For 10 m and 20 m sprint distances, hip-ADD emerged as a significant effect. Mean 505 performance was explained by age, CMJ-impulse, hip-ADD, but also with the addition of NHS. Our findings suggest that insight into the underpinning strength qualities of "running ability" of academy footballers can be obtained from a suite of field-based tests.